Röntgenographische und spektroskopische Untersuchung einiger gemischter Magnesium/Calcium-Fluoroapatite - Apella, María Cristina (1984)
Crystallographic data for mixed apatites of general formula MgₓCa₁₀₋ₓ(PO₄)₆F₂ (x =1-4) have been obtained from X-ray powder data. The unit cell becom es increasingly distorted with the increase of magnesium concentration. The infrared and Raman spectra show that the magnesium incorporation has a negligible effect on the strength of the P - O bonds. The results are discussed in relation with their relevance to the properties of vertebrate hard tissues.